Comparison of a Novel Oxysterol Molecule and rhBMP2 Fusion Rates in a Rabbit Posterolateral Lumbar Spine Model - Scott, Trevor P. (Spine J, 2014)
BACKGROUND CONTEXT: The non-union rate following lumbar spinal fusion is as high as 25%. Bone morphogenetic protein-2 (rhBMP2) has been used as a biological adjunct to promote bony fusion. However, recently there have been concerns about BMP2. Oxysterol 133 (Oxy133) has been shown to promote excellent fusion rates in rodent lumbar spine models and offers a potential alternative to rhBMP2. PURPOSE: The purpose of this study was to compare the fusion rate of rhBMP2 and Oxy133 in a randomized controlled trial using a posterolateral lumbar rabbit spinal fusion model. STUDY DESIGN: This was a randomized control animal study. METHODS: Twenty-four male adult white New Zealand rabbits (3–3.5kg) underwent bilateral posterolateral lumbar spinal fusion at L4–L5. Rabbits were divided into 4 groups: control (A), 30 µg rhBMP2 (B), 20 mg Oxy133 (C), and 60 mg Oxy133 (D). At 4 weeks, fusion was evaluated by fluoroscopy, and at 8 weeks the rabbits were sacrificed and fusion was evaluated radiographically, by manual palpation, and with microCT. Dr. Parhami is a founder and Dr. Stappenbeck is the Director of Chemistry at MAX BioPharma, which has licensed the rights to Oxy133 from UCLA, both have financial interests in the technology presented here. UCLA holds equity in MAX BioPharma. All other authors have no conflicts of interest. Studies reported here were supported in part by the NIH/NIAMS grant RO1AR059794 and in part by MAX BioPharma that purchased the rabbits and provided Oxy133. RESULTS: Fusion rates by radiographic analysis at 8 weeks were: group A 40.0%, group B 91.7%, group C 91.7%, and group D 100%. Evaluation of fusion masses by manual palpation of excised spines after sacrifice showed the following fusion rates: group A 0%, group B 83.3%, group C 83.3%, and group D 90%. MicroCT scanning confirmed these findings. CONCLUSIONS: These findings in a rabbit model demonstrate that both 20 mg dose and 60 mg dose Oxy133 promote fusion that is equivalent to fusion induced by 30 µg rhBMP2 and significantly greater than the control group. The present findings confirm that Oxy133 is a promising candidate for therapeutic development as an alternative to rhBMP2 to promote spinal fusion.